Mental Health Across the Metabolic Spectrum - Vrinda Saxena; Isaac Marin-Valencia (Biological Psychiatry Global Open Science)
Understanding the relationship between metabolism and mental health involves examining how disruptions in one system influence the other. The specific mechanisms by which metabolic processes impact the mind—and how mental well-being, in turn, affects metabolic regulation—are poorly understood. This shortcoming is attributable to the complex and multilayered nature of both the metabolic network and mental processes, as well as the lack of robust quantitative methods to analyze the workings of the mind. Inborn errors of metabolism exemplify this complexity, with over one-fourth being associated with psychiatric manifestations. Despite their high prevalence, psychiatric deficits in individuals with inborn errors of metabolism remain challenging to recognize and manage due to phenotypic variability, limited clinical training in neurometabolism, and gaps in research. To identify intersections between metabolism and mental health, here we assessed the effects of metabolic dysregulation on mental function, focusing on inborn errors of metabolism.